Genetic Evaluation for Hereditary Cancer Syndromes Among African Americans: A Critical Review. (5th March 2022) - Khan, Ambreen; Rogers, Charles R; Kennedy, Carson D; Lopez, AnaMaria; Jeter, Joanne
Abstract: While hereditary cancer syndromes have been described and studied for centuries, the completion of the human genome project fueled accelerated progress in precision medicine due to the introduction of genetic testing in the 1990s, creating avenues for tailored treatments and medical management options. However, genetic testing has not benefited everyone equitably, with nearly all of the published work based on individuals of non-Hispanic White/European ancestry. There remains a gap in knowledge regarding the prevalence, penetrance, and manifestations of common hereditary cancer syndromes in the African-American population due to significant disparities in access and uptake of genetic testing. This review summarizes the available literature on genetic testing for breast, colon, and prostate cancers in the African-American population and explores the disparities in access to genetic testing between non-Hispanic White and African-American patients. This article also addresses the barriers to genetic testing and discrepancies in the uptake of recommendations for hereditary cancer syndromes in the African-American population when compared with non-Hispanic Whites. The review offers practice implications for many healthcare providers and demonstrates gaps in the existing knowledge to be addressed in future studies to help eliminate the persisting health disparities faced by the African-American population. Abstract : The two-fold purpose of this review is to summarize the literature on disparities in genetic evaluation for hereditary breast, colorectal, and prostate cancer syndromes in the African-American population in the United States and to describe areas of study and outreach in this medically underserved population. Barriers to genetic testing are addressed and interventions to improve the utilization of cancer genetics services are highlighted.